PENGARUH TERAPI AKUPUNTUR TERHADAP PENURUNAN NYERI LUTUT PADA PASIEN DENGAN OSTEOARTRITIS - Dodik Keristyanto (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2014)
. Osteoarthritis is a degenerative joint disease that can interfere with the activity and the knee is the most common joints affected. Joint pain is the most common complaint by patients with osteoarthritis complained. Treatment of knee pain in patients with osteoarthritis include pharmacological and non-pharmacological. One non-pharmacologic therapies for pain management in patients with osteoarthritis of the knee is acupuncture therapy. This study aimed to investigate the effect of acupuncture therapy to decrease pain in patients with osteoarthritis of the knee. This research uses Pre experimental design to study the design of one group pre - test and post-test design. Sample size is 46 people with the selection of the sample using incidental sampling technique. Collecting data using questionnaires filled out by the respondents directly, then the scale of pain was measured using a Numerical Rating Scale. The results showed the difference in pain intensity before and after acupuncture therapy. Before therapy acupuncture pain scale is at most weight category is 76.1% and after acupuncture therapy pain scale ever be mild pain category is 87.0%. The results of the Wilcoxon Signed Rank test Test statistic p value <? (0.000 <0.05). It can be concluded that there is a decrease in the effect of acupuncture therapy on knee pain in patients with osteoarthritis in Independent Practice Nurses Latu Usadha Abiansemal.